2016
DOI: 10.1111/nmo.12998
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric rumination subtypes: A study using high‐resolution esophageal manometry with impedance

Abstract: Background The differential diagnosis of intractable reflux in children includes rumination syndrome but confirming the diagnosis using antroduodenal manometry is invasive, costly and requires anesthesia. High resolution esophageal manometry with impedance (HRM-MII) overcomes these limitations and the goal of this study is to validate the use of HRM-MII as a diagnostic tool for rumination and to describe the subtypes of pediatric rumination. Methods We reviewed the HRM-MII tracings of 21 children presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…These include: i) primary rumination of gastric juice, ii) secondary rumination following a reflux episode and/or iii) supra-gastric belching whereby air is repeatedly sucked into the oesophagus and expelled. [29][30][31] The typical protocol to investigate rumination includes a light meal and then a period of observation to detect rumination episodes. Recent studies have also suggested a role for HRM for biofeedback treatment of this condition.…”
Section: Gastro-oesophageal Reflux Diseasementioning
confidence: 99%
“…These include: i) primary rumination of gastric juice, ii) secondary rumination following a reflux episode and/or iii) supra-gastric belching whereby air is repeatedly sucked into the oesophagus and expelled. [29][30][31] The typical protocol to investigate rumination includes a light meal and then a period of observation to detect rumination episodes. Recent studies have also suggested a role for HRM for biofeedback treatment of this condition.…”
Section: Gastro-oesophageal Reflux Diseasementioning
confidence: 99%
“…Whenever possible, additional viscous and solid food swallows are also performed, because subtle motility abnormalities can be uncovered with different textures . If high resolution esophageal manometry is being paired with impedance, all liquids and solids need to have ions to detect impedance changes so added salt or salt water may be required …”
Section: How To Perform the Test?mentioning
confidence: 99%
“…34 If high resolution esophageal manometry is being paired with impedance, all liquids and solids need to have ions to detect impedance changes so added salt or salt water may be required. 35 To assess swallowing function, the patient is given the liquid/ At the end of the single swallows, deglutitive inhibition is measured with the use of repetitive swallows, or with the use of the Rapid Drink Challenge, in which 100-200 mL of fluid are swallowed. 34,36,37 While there are no pediatric studies documenting normal esophageal and bolus pressures in children undergoing the rapid drink challenge, adults studies suggest it increases the sensitive to detect motility disorders, and do support its use to unmask subtle abnormalities which may include abnormalities in pressurization in the esophageal body, elevations in intra-esophageal bolus pressures and elevations in the pressure gradient across the EGJ, all of which may explain the dysphagia.…”
Section: Esophageal Manometrymentioning
confidence: 99%
See 2 more Smart Citations